2013
DOI: 10.5578/mb.6383
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Patterns of Escherichia coli Strains Isolated from Urine Cultures in Turkey: A Meta-Analysis

Abstract: Escherichia coli is the most frequently isolated microorganism from both community-acquired and nosocomial urinary tract infections in Turkey. A large number of studies concerning antibiotic susceptibility of E.coli have been published from different centers throughout the country. The aim of this study was to evaluate the antibiotic resistance patterns of E.coli strains isolated from urine cultures by a meta-analysis in published medical literature between the years of 1996-2012 in Turkey. The study was plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
23

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 7 publications
4
25
0
23
Order By: Relevance
“…In 2012, the overall prevalence in our study among inpatients and outpatients was 44.7% and 22.8%, respectively. The lower rates were reported in outpatients from Turkey (16,17,20). Although in Netherlands, the prevalence of ESBL-producing E. coli in outpatients is lower than our country, there was a significant increasing from 2004 (0.1%) to 2009 (1%) (18).…”
Section: Escherichia Colimentioning
confidence: 73%
See 1 more Smart Citation
“…In 2012, the overall prevalence in our study among inpatients and outpatients was 44.7% and 22.8%, respectively. The lower rates were reported in outpatients from Turkey (16,17,20). Although in Netherlands, the prevalence of ESBL-producing E. coli in outpatients is lower than our country, there was a significant increasing from 2004 (0.1%) to 2009 (1%) (18).…”
Section: Escherichia Colimentioning
confidence: 73%
“…In both inpatients and outpatients, roughly 70% of ESBL producing E. coli were resistant to both trimethoprimsulfamethoxazole and fluoroquinolones. Several studies have been shown fluoroquinolones and trimethoprimsulfamethoxazole to be highly active against E. coli (24-28) in contrast to dramatically decreasing susceptibility rates among ESBL-producers (20,21,25,29). Fluoroquinolone resistance was reported 85% in ESBL producing E. coli isolates in a study in Nepal in 2012 (29) and in 2010 Italian study reported this rate to be even higher (85% -90%) in ESBL-producing E. coli isolates (30).…”
Section: Escherichia Colimentioning
confidence: 93%
“…According to that study, resistance rates of cotrimoxazole and ciprofloxacin were approximately 50% and 55% in outpatients and inpatients, respectively. Again in that study, the resistance rate of ceftriaxone was found to be 25% in inpatients (26).…”
Section: Discussionmentioning
confidence: 99%
“…Üriner sistem enfeksiyonu tedavisinde sıklıkla kullanılan antibiyotiklere direnç oranları bölgesel olarak değişmekle birlikte, E. coli suşlarında 1996-2012 yılları arasın-da siprofloksasin, sefepim, kotrimaksazol ve GSBL oranlarında artış istatistiki olarak anlamlı (3) . Çalışmamızda da GSBL pozitifliği %27.9 olarak saptanmış ve Baykan ve ark.…”
Section: Discussionunclassified